Using Histopathology to Assess the Reliability of Intraoperative Magnetic Resonance Imaging in Guiding Additional Brain Tumor Resection: A Multicenter Study. (18th November 2021) - Shah, Amar S; Yahanda, Alexander T; Sylvester, Peter T; Evans, John; Dunn, Gavin P; Jensen, Randy L; Honeycutt, John; Cahill, Daniel P; Sutherland, Garnette R; Oswood, Mark; Shah, Mitesh; Abram, Steven R; et al.
Graphical Abstract: